2022
DOI: 10.3389/fmicb.2022.1033210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar addition on nitrous oxide emission during soil freeze–thaw cycles

Abstract: Biochar applied to soil can reduce nitrous oxide (N2O) emissions produced by freeze–thaw processes. Nonetheless, how biochar modification affects N2O emissions during freeze–thaw cycles is not completely clear. In our research, during freeze–thaw cycles, microcosm experiments were conducted to investigate the effects of maize straw biochar (MB) or rice straw biochar (RB) addition on soil N2O emissions under different water conditions. The N2O emissions peaked at the initial stage of thawing in all the soils, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Redundancy analysis (Figure 5A) showed that environmental factors explained 82.4% of the variation of the denitrifying bacteria genera in this study, with C/N explaining most of the variation, followed by EC and NO 3 -N. This was similar to previous correlation analyses of soil properties with bacterial communities [38]. It can be concluded that sphagnum substitution significantly alters C/N, EC, and NO 3 − -N, which indirectly affect the variation in denitrifying bacteria genera communities, ultimately resulting in different N 2 O emissions [39]. Correlation heat map analysis (Figure 5B) showed that Rhodanobacter was positively correlated with C/N and EC and negatively correlated with the pH.…”
Section: The Correlation Between Microbial Action and Environmental F...supporting
confidence: 90%
“…Redundancy analysis (Figure 5A) showed that environmental factors explained 82.4% of the variation of the denitrifying bacteria genera in this study, with C/N explaining most of the variation, followed by EC and NO 3 -N. This was similar to previous correlation analyses of soil properties with bacterial communities [38]. It can be concluded that sphagnum substitution significantly alters C/N, EC, and NO 3 − -N, which indirectly affect the variation in denitrifying bacteria genera communities, ultimately resulting in different N 2 O emissions [39]. Correlation heat map analysis (Figure 5B) showed that Rhodanobacter was positively correlated with C/N and EC and negatively correlated with the pH.…”
Section: The Correlation Between Microbial Action and Environmental F...supporting
confidence: 90%
“…A previous study reported that the application of animal manure resulted in a 17.7% increase in N 2 O emissions, while the use of biochar amendments significantly reduced N 2 O emissions by 19.7% (Shakoor et al, 2021). In another experiment conducted in flooded and non-flooded soils during freeze-thaw cycles, the addition of biochar led to a noteworthy decrease in N 2 O emissions, with reductions of up to 67% (Yang et al, 2022b).…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 90%
“…There is growing evidence that these changes in FTC patterns can affect the soil ecosystem. FTCs alter soil structure ( Zhang et al., 2016 ; Zhang et al., 2021 ), water cycling ( Wang et al., 2021 ; Li et al., 2021b ), gas emission ( Hamamoto et al., 2020 ; Yang et al., 2022a ), and litter decomposition ( Pelster et al., 2013 ). Studies have also shown that FTCs affect microbial community structure and function ( Liu et al., 2021 ; Sang et al., 2021 ) and plant root dynamics ( Tierney et al., 2001 ; Sorensen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%